2018
DOI: 10.2147/copd.s166919
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status is associated with muscle strength and quality of life in patients with COPD: a seasonal prospective observation study

Abstract: BackgroundOwing to hospitalization, reduced functional capacity and consequently, less sunlight exposure, suboptimal vitamin D status (25-hydroxyvitamin D [25(OH)D]⩽50 nmol/L) is prevalent among COPD patients.ObjectiveThis study aimed to investigate seasonal changes in vitamin D status and any associated changes in fat-free mass (FFM), muscle strength and quality of life (QoL) in COPD patients.Patients and methodsCOPD patients living in Northern Ireland (n=51) completed study visits at the end of winter (March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…Our results support the findings of previous cross-sectional studies which did not find associations between vitamin D status and general and COPDspecific HR-QOL scores, including EQ-5D scores and the St. George's Respiratory Questionnaire, in COPD patients. [22][23][24] By contrast, it is interesting to observe that in COPD patients, lower concentrations of plasma 25(OH) D 3 contributed to lower lung function, corresponding to increased COPD severity, in agreement with previous studies. [25][26][27][28] Moreover, the multivariate model indicated that the decrease of plasma 25(OH) D 3 level was independently associated with future exacerbations after lung function was added as a covariate.…”
Section: Discussionsupporting
confidence: 90%
“…Our results support the findings of previous cross-sectional studies which did not find associations between vitamin D status and general and COPDspecific HR-QOL scores, including EQ-5D scores and the St. George's Respiratory Questionnaire, in COPD patients. [22][23][24] By contrast, it is interesting to observe that in COPD patients, lower concentrations of plasma 25(OH) D 3 contributed to lower lung function, corresponding to increased COPD severity, in agreement with previous studies. [25][26][27][28] Moreover, the multivariate model indicated that the decrease of plasma 25(OH) D 3 level was independently associated with future exacerbations after lung function was added as a covariate.…”
Section: Discussionsupporting
confidence: 90%
“…A small randomized, placebo-controlled trial of sixty-two patients hospitalized with acute exacerbation of COPD in Iran showed significant improvement in SGRQ total score at day 30 and day 120 following hospital admission, vitamin D supplementation and normalization of vitamin D concentration [21]. Another small trial of fifty-one patients in Northern Ireland showed improved SGRQ total score with higher vitamin D levels [22]. Our data similarly showed vitamin D deficiency was associated with higher SGRQ total score, indicating worse quality of life, and higher MMRC score, consistent with increased dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…Study has shown that muscle strength and quality of life are positively predicted by vitamin-D concentration independent of age, sex, and smoking status. [34] In addition to this, loss in exercise capacity can also be explained by the sarcopenia and loss of muscle strength as a consequence of Vitamin D deficiency. [34]…”
Section: Discussionmentioning
confidence: 99%
“…[34] In addition to this, loss in exercise capacity can also be explained by the sarcopenia and loss of muscle strength as a consequence of Vitamin D deficiency. [34]…”
Section: Discussionmentioning
confidence: 99%